2D Electrides: MXene Phase with C3 Structure Unit: A Family of 2D Electrides (Adv. Funct. Mater. 24/2021). (10th June 2021) - Bae, Soungmin; Espinosa‐García, William; Kang, Yoon‐Gu; Egawa, Noriyuki; Lee, Juho; Kuwahata, Kazuaki; Khazaei, Mohammad; Ohno, Kaoru; Kim, Yong‐Hoon; Han, Myung Joon; Hosono, Hideo; Dalpian, Gustavo M.; et al.
Abstract : In article number 2100009, Gustavo M. Dalpian, Hannes Raebiger, and co‐workers report the discovery of a family of 2D electride materials with composition M2 CO2, where M = Sc, Y, La, Lu, Tm, and Ho. The electride behavior emerges in a new structural phase for MXenes, where the hexagonal carbon layer is broken up into C3 trimers, and anionic electrons get trapped in the voids between the C3 units.